2022
DOI: 10.31234/osf.io/rxm7w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mouthing constructions in 37 signed languages: typology, ecology and ideology

Abstract: Sign languages, like creoles, have been minoritised in linguistics. This makes perspectives on creoles the potential to illuminate the study of sign languages. A common way that sign languages are divided is into deaf and rural groups, based on social criteria. This distinction makes relationships between social and linguistic properties relevant. This paper investigates one such causal relationship, specifically whether extent of contact with spoken language(s) via institutionalised education translates into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…We maintain together with other scholars (Fontana e Fabbretti, 2000;Boyes Braem, 2001;Sutton-Spence, 2001;Crasborn et al, 2008;Roccaforte, 2017;Kusters, 2017;Lin, 2019;Bogliotti and Isel, 2021;Bisnath, 2022) that mouth actions cannot play an external role in lexical access as they function always in correlation with the manual sign and they convey information shaped in relation to the manual sign and to the user"s need. The principal results of this study seem to support the hypothesis that manual gestures and mouth actions act dialectically with the spoken or signed mode of expression and both carry meaning in two different ways.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…We maintain together with other scholars (Fontana e Fabbretti, 2000;Boyes Braem, 2001;Sutton-Spence, 2001;Crasborn et al, 2008;Roccaforte, 2017;Kusters, 2017;Lin, 2019;Bogliotti and Isel, 2021;Bisnath, 2022) that mouth actions cannot play an external role in lexical access as they function always in correlation with the manual sign and they convey information shaped in relation to the manual sign and to the user"s need. The principal results of this study seem to support the hypothesis that manual gestures and mouth actions act dialectically with the spoken or signed mode of expression and both carry meaning in two different ways.…”
Section: Discussionsupporting
confidence: 50%
“…Research based on different kinds of data and on different sign languages (Boyes-Braem, Sutton-Spence, 2001;Bisnath, 2022), has shown that mouthings occur more frequently than mouth gestures and both of them co-occur with the manual sign. Nevertheless, whereas mouth gestures are typically considered a part of sign language, mouthings are viewed as a sociolinguistic phenomenon due to the oral education of most deaf children (Hohenberger and Happ, 2001) and to the situation of bilingualism of most deaf adults (Boyes Braem, 2001;Bogliotti and Isel, 2021) to the interplay of the modalities of signed, spoken and written languages (Bauer, Kyuseva, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following sections briefly survey these types, illustrating the variety of categorisations, definitional criteria, contact situations, and structural outcomes entailed in language contact groups. These groups are idealisations, and the various properties we describe can and have been used to essentialise group members, groups, and language contact itself (Faraclas, 2020;Bisnath, 2023, on de facto prototypes).…”
Section: Types Of Contact Languagesmentioning
confidence: 99%
“…Using the term semiotic resources, as opposed to grammatical features or even linguistic material encourages us to expand the scope of what meaningful material is drawn upon by language users in heterogeneous linguistic contexts, increasing both the descriptive and explanatory power of language contact models. As an example, we draw upon the case study of mouthing in sign 1 languages (Bisnath, 2023) to demonstrate what is gained from such an expansion of scope. We also emphasise the centrality of language users' subjectivities in determining how these semiotic resources are associated with a particular language or variety; this encourages linguists to expect measurable variation within and across language users in terms of where language boundaries are.…”
Section: Introductionmentioning
confidence: 99%